2018
DOI: 10.1097/phh.0000000000000621
|View full text |Cite
|
Sign up to set email alerts
|

A Content Analysis of Nonprofit Hospital Community Health Needs Assessments and Community Benefit Implementation Strategies in Philadelphia

Abstract: Nonprofit hospital community health needs assessments in Philadelphia predominantly identify needs related to access to care and to some extent health behaviors. There is incomplete alignment between the needs identified in hospital assessments and the needs targeted in implementation strategies, underscoring a need for regional coordination in community benefit investments. Improved regional coordination between hospitals serving the region may offer the opportunity to eliminate duplicative efforts and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 12 publications
1
37
0
Order By: Relevance
“…A study contrasting urban and rural obstetric and gynecological practices ( n = 73) in five Pacific Northwest states found that recruitment patterns impacted specialist availability, with urban clinicians seeking partners with more specialized skills and rural clinicians being more likely to leave their practice due to poor specialized care access [92]. Some organizations may choose to limit patient access based on insurance, such as one-third of the counties in a large urban and rural study of mental health facilities ( n = 9696) that did not accept Medicaid [33] or urban non-profit general care hospitals studied in Philadelphia ( n = 15) that should offer more affordable and publically funded substance abuse and mental health services [93]. Organizational culture and leadership also were reported as major mediators in an urban New York needs assessment of integrated primary and behavioral healthcare [72].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study contrasting urban and rural obstetric and gynecological practices ( n = 73) in five Pacific Northwest states found that recruitment patterns impacted specialist availability, with urban clinicians seeking partners with more specialized skills and rural clinicians being more likely to leave their practice due to poor specialized care access [92]. Some organizations may choose to limit patient access based on insurance, such as one-third of the counties in a large urban and rural study of mental health facilities ( n = 9696) that did not accept Medicaid [33] or urban non-profit general care hospitals studied in Philadelphia ( n = 15) that should offer more affordable and publically funded substance abuse and mental health services [93]. Organizational culture and leadership also were reported as major mediators in an urban New York needs assessment of integrated primary and behavioral healthcare [72].…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen-percent of parents of children who required mental healthcare in urban Baltimore, Maryland ( n = 55) reported their family and friends would not support their decision to pursue recommended treatment [75]. Stigma associated with seeking care was identified as a barrier to substance abuse treatment in an urban Philadelphia needs assessment [93] and VHA PTSD treatment in urban Portland, Oregon ( n = 63) [71]. Interviewed obstetric care providers in rural Georgia ( n = 46) found some perceived that lower socioeconomic populations were less likely to adhere to risk-reduction suggestions and more likely to arrive late or miss appointments [64].…”
Section: Resultsmentioning
confidence: 99%
“…Powell et al analyzed the content of 15 CHNAs and 10 CHIPs from 2013 produced by Philadelphia-area hospitals. They found little regional coordination between organizations and the implementation strategies generally overlooked behavioral health and social factors, which often arose at top needs (67).…”
Section: Community Assessment: Contentmentioning
confidence: 99%
“…Coordinating a response across the system may increase the ability to address physical determinants of health, especially with the issue of obesity and related chronic diseases. At the same time, there may be other factors that keep hospitals from pursuing strategies related to physical determinants of health (20), so this issue may require more in-depth study. These findings also point to a need to replicate a study such as the one conducted by Pennel,et al (2) to revisit quality of CHNAs across individual hospitals.…”
Section: Discussionmentioning
confidence: 99%